Institute of Metals Division - Light Emission from GaAsxP1-x Diodes - M. H. Pilkuhn; H. Rupprecht (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1964)
The junction luminescence of GaAsxP1-x diodes containing up to 47 pct Gap was studied. Diodes were prepared by diffusing zinc into n-type material which was eithw boat- or vapor-gvown. Observations concerning the energy and the line shape of the spontaneous emission are presented and discussed; in particular the influence of inhomogeneous phosphorus distribution is considered. The role of reabsorption of the junction radiation is pointed out. With increasing current, the peak emission shifts to higher enwgy. This is alm true in cases where slow line narrowing occurs simultaneously. The length dependence of the threshold current density for lasing at 77 °K was examined for lasers made from the same material. It was found that longer lasers have lower threshold curvent densities, Estimates of the characteristic laser losses are given. Data concwning the range of Gap concentration in which stimulated emission was observed are presented. FORWARD-BIASED p-n junctions in mixed alloys of GaAsxPl-, emit light whose wave length depenfs on the composition of the alloy ranging from 8400A (x = 1) to 5350A (x = 0) at 77°K. Laser action in vapor-grown material was first reported by Holonyak and evacqua,' and in boat-grown material by Ainslie, Pilkuhn, and Rupprecht.' In both cases this was observed for low Gap concentration where GaAs,Pl-, is still a "direct" semiconductor with the lowest conductance-band minimum at k = 0 and a subsidiary minimum in the [loo] direction. As the Gap concentration is increased, the subsidiary [loo] minimum in the conduction band is lowered and finally becomes the lowest minimum for Gap concentrations above 50 pt,3 making the alloy an ''indirect" semiconductor. It is of interest to determine up to which Gap concentration stimulated emission can be observed. EXPERIMENTAL Boat-grown material was prepared by N. Ainslie of IBM by horizontal Bridgman technique. The material was n type and silicon-doped up to a concentration of 10'' cm-'. Vapor-grown material was made by E. Hull of IBM or received from Merck & Co. Diodes were fabricated in a similar manner as in the case of GaAs by zinc diffusion. Details about the diffusion can be found in a later paper.4 All diodes were of Fabry-Perot structure with two parallel sides cleaved and the other two sides sawed. Their width ranged from 50 to 150 p and their length from 50 to 700 p. RESULTS AND DISCUSSION Spectral Distributions. A typical display of the junction luminescence of a GaAsxPl-, diode is shown in Fig. 1. The liquid-nitrogen and room-temperature curves which were taken at a very low current (25 ma dc) show a relatively sharp high-energy emission which is band-edge radiation. They also show a broad low-energy emission which is due to transitions to deep impurity levels. This latter emission line may have different shapes and positions depending on the nature of the material. It can sometimes be quite near the band gap giving rise to "bumps" in the high-energy line. The results presented in this paper will be concerned only with the high-energy emission which becomes more intense relative to the low-energy emission when the current is increased and the temperature is lowered.